The effect of electoral violence on electoral participation in Africa - Shenga,Carlos (2019)
Abstract Systematic African studies have revealed that electoral violence tends to have a negative impact driving Africans away from participating in elections. However, by using a multidimensional approach to electoral violence and electoral participation, combined with a recent dynamic from the 2016 to 2018 Afrobarometer public opinion surveys of 33 African countries, this study finds the opposite. Africans who perceived electoral violence were more likely to attend an election campaign rally and vote. Instead of being used by the incumbent to prevent the opposition supporters from voting, electoral violence appears to motivate those who perceive it to participate. However, whilst election violence may increase electoral participation, this malpractice is not conducive for consolidating democracy or fostering support for, or satisfaction with, democracy.